2017
DOI: 10.1002/ijc.30879
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system tumors and agricultural exposures in the prospective cohort AGRICAN

Abstract: Studies in farmers suggest a possible role of pesticides in the occurrence of Central Nervous System (CNS) tumors but scientific evidence is still insufficient. Using data from the French prospective agricultural cohort AGRICAN (Agriculture & Cancer), we investigated the associations between exposure of farmers and pesticide users to various kinds of crops and animal farming and the incidence of CNS tumors, overall and by subtypes. Over the 2005-2007, 181,842 participants completed the enrollment questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
2
26
1
3
Order By: Relevance
“…These associations could be explained by higher exposure to pesticides of those living close to agricultural areas. A cohort study conducted also in France following more than 181,842 agricultural workers, reported higher risk of central nervous system cancers, including meningioma, among pesticide applicators (Piel et al, 2017). Several toxicological and epidemiological studies have reported increased risk of breast cancer among women exposed to pesticides (Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These associations could be explained by higher exposure to pesticides of those living close to agricultural areas. A cohort study conducted also in France following more than 181,842 agricultural workers, reported higher risk of central nervous system cancers, including meningioma, among pesticide applicators (Piel et al, 2017). Several toxicological and epidemiological studies have reported increased risk of breast cancer among women exposed to pesticides (Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, these workers also are exposed to other factors such as pesticides and extreme temperatures. These exposures, along with vibration, may increase the risk of developing certain cancers, respiratory problems and neurodegenerative diseases (Suratman, Edwards,Babina 2015; Manyilizu et al 2016; Kachuri et al 2017; Bencko,Yan Li Foong 2017; Prado et al 2017; Piel et al 2017; Darcey et al 2018; Prudente et al 2018; Ramirez-Santana et al 2018; Anderson et al 2018). Studies need to be performed to determine how exposure to these various factors affect the risk of developing these vibration-induced illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…The Agricultural Health Study in the USA found a signi cant fourfold increase in farmers most exposed to chlorpyrifos (Lee et al 2004) and a threefold increase in their spouses using domestic or occupational organochlorines (Louis et al 2017). In the French Agrican cohort, elevated risks were observed in farmers exposed to speci c crops (peas, beets, potatoes) and risk doubled in those who applied pesticides (Piel et al 2017). Analysis focused on carbamate insecticides, fungicides and herbicides pointed to some speci c active ingredients being associated with a high increase in the risk (Piel et al 2019a(Piel et al , 2019b.…”
mentioning
confidence: 99%